Relevansi Sistem Full Day School dengan Pendidikan Karakter Anak - Izza, Ismatul (LP3M Universitas Islam Zainul Hasan Genggong, 2017)
The Full Day School system is one of the school programs where students studyfull day at school. Learning begins at 07.00 pm until at 15.00 pm, EducationMinister of Education initiated Full Day School’s learning system is aimedbesides full learning in school also aims to get the students get charactereducation. As the world grows, education now begins to improve the qualityof students’ resources in various ways. It departs from the many “demands”to become a rich man of science and balanced with skill that qualified. Oneof his strategies is full day school. The formation of character for every humanbeing is a duty that must be done continuously, either through coaching,habituation, and things that can increase one’s ahlak. School participation inthe organization of the Full Day School System also determines the quality ofeducational outcomes for children’s character. So the relevance of these twocomponents can be expressed if the goal of education is achieved as designedby the school, packed with precise and child friendly, facilities and infrastructureto support, qualified and prosperous educators.